Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1002/(sici)1097-0215(19970904)72:5<720::aid-ijc3>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pregnancy on the outcome of breast cancer: A case‐control study

Abstract: The relationship between pregnancy and the outcome of breast cancer remains controversial. The purpose of this study was to determine the prognostic value of pregnancy at the time of diagnosis of primary infiltrating breast cancer. In a retrospective multi-center study we compared a group of 154 patients presenting pregnancy-associated (PA) breast cancer with a control group of 308 patients presenting non-pregnancyassociated (non-PA) breast cancer. Classic prognostic factors, treatment modalities, disease-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 16 publications
(18 reference statements)
0
32
1
5
Order By: Relevance
“…A study by Bonnier et al (9), in addition to other studies, suggested that pregnancy may be an independent prognostic factor. This was a multi‐institutional study carried out in 23 French institutions.…”
Section: Prognosismentioning
confidence: 92%
See 4 more Smart Citations
“…A study by Bonnier et al (9), in addition to other studies, suggested that pregnancy may be an independent prognostic factor. This was a multi‐institutional study carried out in 23 French institutions.…”
Section: Prognosismentioning
confidence: 92%
“…The majority of PABCs are high grade and lymphovascular invasion is often present, characteristics that are similar to those seen in young non‐pregnant breast cancer patients (7,8). However, when further histological comparisons are made with non‐pregnant controls, studies show that tumors in PABC are 1.5–2 times more often over 2 cm in diameter and lymph node‐positive, and 2.5 times more often associated with distant metastases at diagnosis (9–12). It is unknown whether this is caused by a more aggressive growth pattern due to the biological effects of pregnancy, to delayed diagnosis, or to a combination of the two (13).…”
Section: Pabc Pathologymentioning
confidence: 99%
See 3 more Smart Citations